The linguistics structure and implication of Chinese Malaysian wedding dish names - Ang, Lay Hoon; Ng, Man Ling; Lam, Kai Chee (Bagui Overseas Chinese, 2016)
In Malaysia,Chinese dishes are served in most Chinese wedding. The name of dishes is a continuation of practice in China in terms of structure and element. The wedding dishes still retain the tradition to improvise 1-5 elements side by side. Apart from cooking method in the form of verbs,the other mostly nouns. Wedding dishes also take into account the ethnic and cultural psychology,exhibit extreme richness,happiness and auspicious meaning. Most dishes consist of 4-13 words,formed by using actual or virtual elements or combining both.The diversity of names reflects the high requirement of Chinese people to language use in wedding.